The development of methods for rapid prediction of frost resistance of ceramic products/Keraminių gaminių atsparumo šalčiui sparčiųjų prognozavimo metodų raida - Kičaitė, Asta (Journal of Civil Engineering and Management, 1999)
One of important parameters determining the quality of ceramic products is the resistance to frost. Frost resistance of ceramic brick can be determined exactly by direct unilateral freezing methods. Investigations by these methods last from some days to several months. Therefore rapid prediction methods become more important. Rapid methods for predicting frost resistance of ceramic products give more detailed data if chosen properties of materials that reflect better destructive action of water during freezing in a ceramic body are more exact. Nowadays the methods for rapid prediction are divided according to the quantity of parameters used for prediction and according to the established characteristics. The prediction of frost resistance of ceramic products can be carried out using a parameter or some parameters. The prediction methods using some parameters are divided into three groups: 1) the prediction of frost resistance of ceramic products according to the size of pores and their distribution; 2) the prediction for frost resistance of ceramic products according to physical, mechanical and structural properties; 3) the prediction for frost resistance of ceramic products according to structural and deformation properties. The analysis leads to the following conclusions: – for prediction of frost resistance of ceramic products during the service life, it is necessary to use methods based on unilateral freezing; – rapid methods of prediction based on usage of more parameters are much more reliable and better correspond to frost resistance of ceramic products; – rapid methods of prediction allow to determine quickly frost resistance and to stop the delivery of poor products to construction sites; – dilatometric methods are more comfortable and therefore more prospective. Article in Lithuanian. First Published Online: 26 Jul 2012